Konkurencyjność przedsiębiorstw sektora rolno-spożywczego: Companies competitiveness of the agri-food sector - Dolata, Małgorzata; Hadryjańska, Barbara (Management and Administration Journal, 2021)
In the article were presented the factors of competitiveness of Polish enterprises in the agri-food industry. Description includes of competitiveness as a system consisting of four basic elements: potential competition, competitive advantage, the instruments of competition and competitive position. The factors influencing the competitiveness of enterprises and attributes competitiveness were presented. It was discussed also the meaning and specificity of agrifood sector in shaping the competitiveness of companies operating in it.